Exploring the Cycle Period and Parity of Stellar Magnetic Activity with Dynamo Modeling - Hazra G.; Jiang J.; Karak B.B.; Kitchatinov L. (My University, 2025)
Observations of chromospheric and coronal emissions from various solar-type stars show that the stellar magnetic activity varies with the rotation rates of the stars. The faster the star rotates, the stronger its magnetic activity becomes, but the activity cycle period does not show a straightforward variation with the rotation rate. For slowly rotating stars, the cycle period decreases with the increase in rotation rate, while for the fast rotators, the dependency of cycle period on rotation is presently quite complicated. We aim to provide an explanation of these observational trends of stellar magnetic activity using a dynamo model. We construct a theoretical dynamo model for stars of mass 1 M o˙ based on the kinematic flux transport dynamo model including radial pumping near the surface of the stars. The inclusion of this near-surface downward radial pumping is found to be necessary to match the observed surface magnetic field in the Sun. The main ingredients of our dynamo model, meridional circulation and differential rotation for stars, are obtained from a mean-field hydrodynamic model. Our model shows a decrease in cycle period with increasing rotation rate in the slowly rotating regime and a slight increase in cycle period with rotation rate for the rapid rotators. The strength of the magnetic field is found to increase as the rotation rate of the star increases. We also find that the parity of the stellar magnetic field changes with rotation. According to our model, the parity flips to quadrupolar from dipolar if the rotation period of the star is less than 17 days. © 2019 The American Astronomical Society. All rights reserved.